Aunt Dimity and the Village Witch - Atherton, Nancy (Atherton, Nancy. Aunt Dimity series., 2013)
"Nancy Atherton's seventeenth cozy mystery featuring the beloved Aunt Dimity-the original paranormal detective. When Amelia Thistle moves to Finch, her new neighbors welcome her with open arms-and inquiring minds. Among them is Lori Shepherd, who isn't fooled by Amelia's unassuming persona. Amelia is, in fact, a world-famous artist with a rabid and eager-to-stalk fan base. In order to keep peace in Finch, Lori must help Amelia conceal her identity. Amelia, meanwhile, sets about working on the riddle that brought her to town in the first place. A fragment of a family diary hints that one of Amelia's ancestors might have been Mistress Meg, the Mad Witch of Finch. Following the clue, Lori hunts through Finch's darkest and most secret corners, all the while dodging nosy neighbors and Amelia's frantic fans. With Aunt Dimity's otherworldly help, Lori inches closer to the true story of Mistress Meg-and Amelia. Returning to the charming world of Finch, Nancy Atherton's latest novel is sure to delight faithful Aunt Dimity readers, Anglophiles, and cozy mystery fans."--